The effect of an educational intervention based on protection motivation theory on prostate cancer prevention behaviors in men 50 to 75 years old - Vahid Khosravi; Majid Barati; Babak Moeini; Younes Mohammadi (Tehran University of Medical Sciences, 2019)
Background & Aim: Prostate cancer is one of the most common causes of death from cancers in men. The aim of this study was to determine the effect of an educational intervention based on protection motivation theory (PMT) on prostate cancer prevention behaviors in men 50 to 75 years old. Methods & Materials: This study is a randomized controlled trial with control group conducted on 100 men referred to the retirement centers in Hamadan in 2017. Participants were selected by convenience sampling method and randomly divided into two experimental (n=50) and control groups (n=50). A self-administered questionnaire including demographic information and PMT constructs was completed by the participants. Educational intervention was administered over four sessions in the experimental group. The questionnaires were completed by the two groups two months after the intervention. Data were analyzed by the SPSS software version 16 using independent t-test, Chi-square and the analysis of covariance. Results: Before the intervention, the two groups were homogeneous in terms of demographic characteristics and the PMT constructs (perceived rewards, perceived response cost, fear, perceived self-efficacy), and cancer screening behavior. The intervention could improve all the PMT constructs in the experimental group compared to the control group. Also, Prostate-Specific Antigen (PSA) screening behavior was 38(76) in the experimental group and 16(32) in the control group (P<0.001). Conclusion: The results of the study showed that protection motivation theory can be used as a framework for designing educational programs to perform prostate cancer screening.